Pola Asuh Orang Tua dalam Membina Akhlak Anak di Desa Sidoluhur Lampung Tengah - Dwi Noviatul Zahra; Muhammad Afif Amrulloh (ISTAWA, 2018)
Parents in the family have an important task that is seeking first coaching because the personality of parents will be a reflection for the realization of the personality of children, especially mothers who are the most basic joints in the family. Therefore, this study aims to determine the parenting of parents in fostering morals in Sidoluhur Village children. The type of research used is descriptive research. This research is field research, in collecting author data using main method that is: interview, and method of supporting observation and documentation, then analyzed by using deductive analysis. Based on the result of research, it is found that parenting pattern in fostering morality of children by exemplary, custom, advice, attention and punishment. Parents have tried to give moral coaching as much as possible but there are still doing bad morals such as lying, taking the rights of others, fighting, denied the elderly.